Deep learning model for predicting immunotherapy response in patients with advanced NSCLC: Study findings demonstrate a strong and independent deep learning‐based feature associated with an immune checkpoint inhibitor response in patients with NSCLC across cohorts - Nierengarten, Mary Beth (Cancer, 2025)
This news section offers Cancer readers timely information on events, public policy analysis, topical issues, and personalities. In this issue, study findings demonstrate a strong and independent deep learning‐based feature associated with an immune checkpoint inhibitor response in patients with NSCLC across cohorts. In addition, cabozantinib was found to significantly improve progression‐free survival in a heavily pretreated population of patients with advanced neuroendocrine tumors, and a new standard of care is discussed for patients with asymptomatic brain metastases from melanoma.